Numerical Simulation of a Cylindrical Outer Flanging Spinning - Yang, Xuhui; Jia, Zhen (Manufacturing Technology Journal, 2024)
The use of spinning technology for the outer flanging of cylindrical parts can save moulds, reduce labour intensity, and improve production efficiency. Therefore, two finite element models for the outer flanging spinning with the flange radius of 4 mm and 5 mm are established in this article. The deformation process, stress-strain field, and wall thickness distribution of the flange during the spinning period are analyzed. It can be found from the simulation results that, the blank of both working conditions cannot fit the contour of the roller until the until 2.5 s before the end of the spinning process, and it is more difficult to achieve fitting with a smaller profiling radius of 4 mm. The x-direction force caused by the 4mm profiling radius is less than that by the 5mm one before the end of forming due to the smaller contact area with the roller. According to deformation in a relatively cramped area, the wall thickness distribution under the condition with a larger curvature is generally slightly greater than that with a smaller one.
Keywords: Cylindrical thin-wall part; Flanging spinning; Numerical simulation; Metal flow; Contour fit degree